Nonlinear analysis of stability for imperfect eccentrically stiffened FGM plates under mechanical and thermal loads based on FSDT. Part 1: Governing equations establishment - Dung, Dao Van; Nga, Nguyen Thi (Vietnam Journal of Mechanics, 2015)
In this paper, the buckling and post-buckling behaviors of eccentrically stiffened functionally graded material (ES-FGM) plates on elastic foundations subjected to in-plane compressive loads or thermal loads are investigated by an analytical solution. The novelty of this work is that FGM plates are reinforced by FGM stiffeners and the temperature, stiffener, foundation are considered. The first-order shear deformation plate theory is used. The thermal elements of plate and stiffeners in fundamental equations are introduced. Theoretical formulations based on the smeared stiffeners technique and the first-order shear deformation plate theory, are derived. The analytical expressions to determine the static critical buckling load and post-buckling load-deflection curves are obtained.